Variability of the surface boundary layer of reef-building coral species - Martins, Catarina P. P.; Wall, Marlene; Schubert, Patrick; Wilke, Thomas; Ziegler, Maren; Justus Liebig University Giessen (My University, 2024)
The coral-seawater interface is an important, highly dynamic microenvironment for reef-building corals. Also known as the concentration boundary layer (CBL), it is a thin layer of seawater bordering the coral surface that dictates the biochemical exchange between the coral colony and bulk seawater. The CBL is thus a key feature that modulates coral metabolism. However, CBL variation among small-polyped coral species remains largely unknown. Therefore, we recorded over 100 profiles of dissolved O2 concentration using microsensors to characterize CBL traits (thickness, surface O2 concentration, and flux) of three small-polyped branching coral species, Acropora cytherea, Pocillopora verrucosa, and Porites cylindrica. Measurements were conducted during light and darkness combined with low or moderate water flow (2 and 6 cm s−1). We found that CBL traits differed among species. CBL thickness was lowest in A. cytherea, while P. verrucosa showed the largest depletion of surface O2 in dark and highest dark flux. In addition, we found that O2 concentration gradients in the CBL occurred with three main profile shapes: diffusive, S-shaped, and complex. While diffusive profiles were the most common profile type, S-shaped and complex profiles were more frequent in P. verrucosa and P. cylindrica, respectively, and prevailed under low flow. Furthermore, profile types differed in CBL thickness and flux. Finally, low flow thickened CBLs, enhanced changes in surface O2 concentration, and reduced flux, compared to moderate flow. Overall, our findings reveal CBL variability among small-polyped branching corals and help understand CBL dynamics in response to changes in light and water flow conditions.
Keywords: ddc:570